Non-surgical treatment of transverse deficiency in adults using Microimplant-assisted Rapid Palatal Expansion (MARPE) - Brunetto,Daniel Paludo (2017)
ABSTRACT Introduction: Maxillary transverse deficiency is a highly prevalent malocclusion present in all age groups, from primary to permanent dentition. If not treated on time, it can aggravate and evolve to a more complex malocclusion, hindering facial growth and development. Aside from the occlusal consequences, the deficiency can bring about serious respiratory problems as well, due to the consequent nasal constriction usually associated. In growing patients, this condition can be easily handled with a conventional rapid palatal expansion. However, mature patients are frequently subjected to a more invasive procedure, the surgically-assisted rapid palatal expansion (SARPE). More recently, researches have demonstrated that it is possible to expand the maxilla in grown patients without performing osteotomies, but using microimplants anchorage instead. This novel technique is called microimplant-assisted rapid palatal expansion (MARPE). Objective: The aim of the present article was to demonstrate and discuss a MARPE technique developed by Dr. Won Moon and colleagues at University of California - Los Angeles (UCLA). Methods: All laboratory and clinical steps needed for its correct execution are thoroughly described. For better comprehension, a mature patient case is reported, detailing all the treatment progress and results obtained. Conclusion: It was concluded that the demonstrated technique could be an interesting alternative to SARPE in the majority of non-growing patients with maxillary transverse deficiency. The present patient showed important occlusal and respiratory benefits following the procedure, without requiring any surgical intervention.